A combined "eat me/don't eat me" strategy based on extracellular vesicles for anticancer nanomedicine. Issue 1 (19th August 2020) - Belhadj, Zakia; He, Bing; Deng, Hailiang; Song, Siyang; Zhang, Hua; Wang, Xueqing; Dai, Wenbing; Zhang, Qiang
ABSTRACT: A long‐term and huge challenge in nanomedicine is the substantial uptake and rapid clearance mediated by the mononuclear phagocyte system (MPS), which enormously hinders the development of nanodrugs. Inspired by the natural merits of extracellular vesicles, we therefore developed a combined "eat me/don't eat me" strategy in an effort to achieve MPS escape and efficient drug delivery. Methodologically, cationized mannan‐modified extracellular vesicles derived from DC2.4 cells were administered to saturate the MPS (eat me strategy). Then, nanocarriers fused to CD47‐enriched exosomes originated from human serum were administered to evade phagocytosis by MPS (don't eat me strategy). The nanocarriers were also loaded with antitumor drugs and functionalized with a novel homing peptide to promote the tumour tissue accumulation and cancer cell uptake (eat me strategy). The concept was proven in vitro as evidenced by the reduced endocytosis of macrophages and enhanced uptake by tumour cells, whereas prolonged circulation time and increased tumour accumulation were demonstrated in vivo . Specially, the strategy induced a 123.53% increase in tumour distribution compared to conventional nanocarrier. The study both shed light on the challenge overcoming of phagocytic evasion and provided a strategy for significantly improving therapeutic outcomes, potentially permitting active drug delivery via targeted nanomedicines.